Impact of cervical osteoarthritis on quality of life after free flap reconstruction in head and neck cancer - Li, Yili; Du, Wei; Zhang, Xu; Yuan, Junhui; Sun, Yibao; Shao, Zhe; Chen, Shuang; Dai, Yaojun; Zhou, Xiaoguang; Yang, Yong; Mei, Wei (Frontiers in Oncology, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) often requires free flap reconstruction, which involves extensive cervical manipulation. Concurrently, cervical osteoarthritis is increasingly prevalent due to modern lifestyle factors. This study investigates the impact of cervical osteoarthritis on quality of life (QoL) in HNSCC patients undergoing free flap reconstruction.MethodsA retrospective analysis of HNSCC patients who underwent free flap reconstruction was conducted. Patients were stratified by cervical osteoarthritis status and assessed using the Neck Disability Index (NDI), EORTC QLQ-C30, and QLQ-HN35 questionnaires at preoperative, postoperative, and follow-up intervals (3, 6, and 12 months post-adjuvant therapy). Propensity score matching (1:1) adjusted for confounding factors.ResultsA total of 60 patients were analyzed. At baseline, cervical osteoarthritis was associated with lifting dysfunction (p=0.004) and nausea/vomiting (p<0.05). Postoperatively, transient impairments in driving, sleeping, and swallowing were noted in the osteoarthritis group, particularly within 3 months (p<0.05). Persistent fatigue was reported, but emotional function scores were superior in this group (p<0.05). No significant differences in QoL were observed based on osteoarthritis subtype. Response rates declined over time, primarily due to cancer recurrence.ConclusionsCervical osteoarthritis correlates with transient postoperative functional impairments and persistent fatigue but does not adversely affect long-term QoL. Emotional resilience in these patients suggests adaptive coping mechanisms. These findings underscore the need for targeted preoperative counseling and rehabilitation to address short-term challenges while leveraging patients’ psychosocial strengths. This study provides critical insights for optimizing patient-centered care in HNSCC reconstruction.